1996
DOI: 10.1017/s0022112096000468
|View full text |Cite
|
Sign up to set email alerts
|

Topological interpretation of the surface flow visualization of conical viscous/inviscid interactions

Abstract: The asymptotic flow structure is considered for a viscous–inviscid conical interaction, in particular that between a swept shock wave and a boundary layer. A flow model is devised based on the three-layer interaction concept. Assuming conicity of the inviscid flow regions, a viscous layer structure is established that is compatible with the inviscid outer flow, and which produces a geometrically conical surface flow pattern. This result is obtained from a dimensional analysis, which reveals similarity of the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Panaras (1996) reviewed the work of Kubota & Stollery (1982) and Alvi & Settles (1992); analysis has been provided by van Oudheusden, Nebbeling & Bannink (1996). The fin is a wedge that is mounted on a sidewall.…”
Section: Previous Related Sbli Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Panaras (1996) reviewed the work of Kubota & Stollery (1982) and Alvi & Settles (1992); analysis has been provided by van Oudheusden, Nebbeling & Bannink (1996). The fin is a wedge that is mounted on a sidewall.…”
Section: Previous Related Sbli Researchmentioning
confidence: 99%
“…In steady, laminar, incompressible flows, it has been shown that limiting streamlines are identical to skin friction lines and oil streak lines (van Oudheusden et al 1996). Squire (1961) has demonstrated that oil film lines are accurate markers of the skin friction lines in steady flows.…”
Section: Brief Review Of Critical Point Theorymentioning
confidence: 99%
“…This flow field is characterised by the separation line, upstream influence and reattachment line. 9 This fin induced flow has been found to have a dominant effect on the flow studied at present. The flow topology of the interaction similar to the present condition is given by Eagle et.al.…”
Section: Figure 1 Typical Shock-wave Boundary Layer Interaction Nearmentioning
confidence: 80%
“…A typical schematic of surface flow from flow visualization experiments is shown in Fig.2. The surface flow pattern formed by a sharp fin is conical(Lu, 1993;Settles and Dolling, 1992;Oudheusden et al, 1996), and not cylindrical(Johnston, 1960;Myring, 1977;Knight et al, 1992;Van Oudheusden et al, 1996). The topological pattern of the surface streamlines in conical interactions has been interpreted recently by Van Oudheusden et al(1996).In Fig.2, the schematic surface pattern depicts a geometric conicity, in that rays are shown emanating from a certain origin close to the fin apex.…”
mentioning
confidence: 81%
“…As a result, this convergence line is formed before it becomes parallel to the shock as the shock wave angle increases. Van Oudheusden et al (1996) argued that the far field of the conical interaction does not possess a quasi-two dimensional structure in the cross-flow plane of the radial direction. They showed that the conicity of the inviscid flow regions in supersonic flow produces a geometrically conical surface flow pattern.…”
Section: Physical Mechanism For Incipient Separationmentioning
confidence: 99%